2004
DOI: 10.1152/ajpcell.00463.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T-type calcium current and its contribution to electrical activity in rabbit urethra

Abstract: Rabbit urethral smooth muscle cells were studied at 37 degrees C by using the amphotericin B perforated-patch configuration of the patch-clamp technique, using Cs(+)-rich pipette solutions. Two components of current, with electrophysiological and pharmacological properties typical of T- and L-type Ca(2+) currents, were recorded. Fitting steady-state inactivation curves for the L current with a Boltzmann equation yielded a V(1/2) of -41 +/- 3 mV. In contrast, the T current inactivated with a V(1/2) of -76 +/- 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
5
39
1
Order By: Relevance
“…Both L-type and T-type Ca 2+ -currents have been recorded in isolated myocytes. Blockade of the former type reduced the number of APs in each burst; the frequency within bursts was attenuated by blockade of T-type current (Bradley et al, 2004). However, both channels represent targets that may modulate spontaneous activity.…”
Section: Muscles Of the Urethramentioning
confidence: 98%
“…Both L-type and T-type Ca 2+ -currents have been recorded in isolated myocytes. Blockade of the former type reduced the number of APs in each burst; the frequency within bursts was attenuated by blockade of T-type current (Bradley et al, 2004). However, both channels represent targets that may modulate spontaneous activity.…”
Section: Muscles Of the Urethramentioning
confidence: 98%
“…Because of these gating properties, the importance of T-type currents in the regulation of smooth muscle membrane potential is a matter of controversy. However, there is evidence from the rabbit urethra that, at least in this tissue, T-type channels regulate action potential frequency (Bradley et al 2004). …”
Section: Imaging Intracellular Ca 2þmentioning
confidence: 99%
“…Most current knowledge regarding the role of ion channels in the urethra has come from isometric tension recordings, [25][26][27][28][29][30][31] sharp microelectrode recordings of intact preparations, 25,27,32,33 and the patch clamp technique. [29][30][31][33][34][35][36][37][38][39][40] Earlier studies measuring electrical and mechanical (i.e., force) activity in rabbit urethral smooth muscle reported that the spontaneous activity was in fact myogenic in nature, 25,41 resembling the activity seen in the GI tract. 42 Thus, the excitability appeared to be driven by a form of pacemaker originating within the muscle itself.…”
Section: 24mentioning
confidence: 99%
“…76,77 This has certainly proved to be consistent with action potential spike events observed in urethral smooth muscle cells. 30,31,33,39,78 It is well-established that the L-type (long-lasting) VGCCs activate at more depolarized potentials than their T-type (transient-lasting) counterpart. 76 It was also previously demonstrated that L-type VGCC current was crucial for generating and maintaining urethral tone in intact preparations.…”
Section: Vgccs In Urethral Smooth Musclementioning
confidence: 99%
See 1 more Smart Citation